Improving The Students’ Writing Competence in a Second Language Acquisition through The Implementation of Lesson Study - Syahfitri Purnama (JETL (Journal of Education, Teaching and Learning), 2017)
Writing is the most difficult skill for second language learners. It can be seen, for example, they always make ageneralization, simplification, less of knowing vocabularies, punctuation, spelling,  and grammar. This paper will describe improving the students’ writing competence in second language acquisition through the implementation of lesson study in faculty of language education of Indraprasta PGRI University of Jakarta. This research uses qualitative approach and the data taken from the students who are studying writing in the class. In applying lesson study, lecturer model explains  about the materials based on the syllabus of the subject.  The students are also given tasks in their groups. The observers watch and write about the students and assist them. After doing this, the observers discuss about the class with the lecturer model.  By doing the implementation of  Lesson Study, the students can work in group together, the class is so inspiring, they feel satisfied with the explanation of the lecturer model and  havegood impact to improve the students’ writing competence.